Perception of Parenting Practices in Pesantren Al-Ittifaqiyah Through the Eyes of Santri - Asep Jahidin; Yusuf Albana; Idan Ramdani; Sindy Shofa Dermawati (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The Islamic boarding school (pesantren) caregiver of Santri is a widely ignored issue in the management of Pesantren as an Islamic educational institution that requires Santri to live and participate in various daily activities. This study examines how the thoughts and ideas of pesantren relate to the parenting of santri based on the phenomenon in Pesantren Al-Ittifaqiyyah, Indralaya, Ogan Ilir, South Sumatra. By analyzing the conceptual problems of adolescent Santri's perspectives on pesantren parenting and communication built into the implementation of parenting in the pesantren, a parenting institution, Data collection was carried out through in-depth interviews with adolescent Santri living in Pesantren, caregivers in Pesantren, and leadership elements in Pesantren. Document searches and studies were also conducted, including reviewing archives, physical devices, conducting field observations, and participant observations. The results showed that the santri's views on parenting and its forms of communication in pesantren have a variety of dimensions in the parenting process in pesantren, including six dimensions, namely warmth, rejection, rules, conflict, freedom, support, and coercion, as well as the typical dimensions of pesantren, namely religion, independence, and administration. Communication is the key to establishing a parenting pattern that includes these dimensions when carrying out parenting in the pesantren environment.